2020
DOI: 10.1101/2020.03.24.004911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An allosteric interaction controls the activation mechanism of SHP2 tyrosine phosphatase

Abstract: SHP2 is a protein tyrosine phosphatase with a key role in multiple signaling pathways, including the RAS-MAPK cascade. Germline mutations in PTPN11, the gene encoding SHP2, occur in 50% of individuals affected by Noonan syndrome, whereas somatic mutations in this gene cause more than 30% of cases of juvenile myelomonocytic leukemia (JMML), and are variably found in other pediatric hematologic malignancies and tumors. Inhibition of the wild-type protein has been recently demonstrated as a novel effective therap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Notably, the "allosteric switch" model has been so far unable to convincingly explain the pathogenicity of the Thr42Ala substitution, in terms of either enhancement of the binding cleft opening or formation of additional favorable contacts with the phosphopeptide [15]. Instead, owing to the reduced propensity of alanine for β-sheet as compared to threonine [57], the α-β model attributes to the Thr42Ala substitution the effect of destabilizing the central β-sheet, thereby rendering N-SH2 more prone to adopt the activating α-state [43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, the "allosteric switch" model has been so far unable to convincingly explain the pathogenicity of the Thr42Ala substitution, in terms of either enhancement of the binding cleft opening or formation of additional favorable contacts with the phosphopeptide [15]. Instead, owing to the reduced propensity of alanine for β-sheet as compared to threonine [57], the α-β model attributes to the Thr42Ala substitution the effect of destabilizing the central β-sheet, thereby rendering N-SH2 more prone to adopt the activating α-state [43].…”
Section: Discussionmentioning
confidence: 99%
“…activation. In fact, previous molecular dynamics simulations suggested that the complete displacement of N-SH2 away from the PTP active site requires an energy in the order of 70 kJ/mol [41,43]. Hence, it is unlikely that rearrangement of the binding cleft are sufficient to drive SHP2 activation.…”
Section: Binding Cleft Opening Is Favored In Autoinhibited Shp2 In Watermentioning
confidence: 98%
See 3 more Smart Citations